Scolopendra Pharmacopuncture Ameliorates Behavioral Despair in Mice Stressed by Chronic Restraint - Yu-Jin Choi; Hwa-Young Lee; Yunna Kim; Seung-Hun Cho (Korean Pharmacopuncture Institute, 2017)
Introduction:Pharmacopuncture, which combines acupuncture with herbal medicine, is one of the newly developed acupuncture techniques that has recently been put into use. The possible mechanisms of scolopendra pharmacopuncture, as well as its potential effects on depressive symptoms, were investigated in this study by using a mouse model of chronic immobilization stress (CIS).Methods:C57BL/6 male mice were randomly assigned into three groups: mice not stressed with restraint and injected with distilled water, mice stressed with restraint and injected with distilled water, and mice stressed with restraint injected with scolopendra pharmacopuncture at a cervical site. Behavioral tests (an open field test, tail suspension test, and forced swimming test) were carried out after two weeks of CIS and injection treatments. The expression levels of glial fibrillary acidic protein (GFAP) in the hippocampus were determined by using western blot and immunohistochemistry analyses.Results:Mice exposed to CIS showed decreased behavioral activity, while scolopendra pharmacopuncture treatment significantly protected against the depressive-like behaviors induced by CIS. Moreover, scolopendra pharmacopuncture treatment increased GFAP protein levels in the hippocampi of the mice stressed by chronic immobilization.Conclusion:Scolopendra pharmacopuncture has an ameliorating effect on depressive behavior, which is partially mediated through protection against glial loss in the hippocampus.